DNA Methylation Analyses Unveil a Regulatory Landscape in the Formation of Nacre Color in Pearl Oyster Pinctada fucata martensii - Wang, Ziman; Zhu, Shaojie; Yin, Shixin; Zhao, Zihan; Zheng, Zhe; Deng, Yuewen (Frontiers in Genetics, 2022)
Pearl color is regulated by genetics, biological pigments, and organic matrices and an important factor that influences pearl economic value. The epigenetic regulation mechanism underlying pearl pigmentation remains poorly understood. In this study, we collected the mantle pallial (MP) and mantle central (MC) of the golden-lipped strain, and MP of the silver-lipped strain of pearl oyster Pinctada fucata martensii. The whole-genome bisulfite sequencing (WGBS) technology was employed to investigate the possible implication of epigenetic factors regulating nacre color variation. Our results revealed approximately 2.5% of the cytosines in the genome of the P. fucata martensii were methylated, with the CG methylation type was in most abundance. Overall, we identified 12, 621 differentially methylated regions (DMRs) corresponding to 3,471 DMR-associated genes (DMGs) between the two comparison groups. These DMGs were principally enriched into KEGG metabolic pathways including ABC transporters, Terpenoid backbone biosynthesis, and Fatty acid degradation. In addition, integrating information about DMGs, DEGs, and function annotation indicated eight genes LDLR, NinaB, RDH, CYP, FADS, fn3, PU-1, KRMP as the candidate genes related to pigmentation of nacre color. The further study proved that the pigment in nacre is violaxanthin. The results of our study provide support that there is an association between nacre color formation and DNA methylation profiles and will help to reveal the epigenetic regulation of nacre pigmentation formation in pearl oyster P. fucata martensii.